2019
DOI: 10.1086/704059
|View full text |Cite
|
Sign up to set email alerts
|

Are Pheromones Key to Unlocking Cryptic Lizard Diversity?

Abstract: Animals use mating traits to compete for, attract, and choose mates. Because mating traits influence mate choice, the divergence of mating traits between populations can result in reproductive isolation. This can occur without associated morphological divergence, producing reproductively isolated cryptic species that are visually indistinguishable. Thus, identifying the mating traits in morphologically conservative groups is key to resolving diversity and speciation processes. Lizards contain many such groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 72 publications
5
35
0
3
Order By: Relevance
“…Under this LRC model, we can extrapolate that sexually monochromatic species that share a common mate-choice strategy may be more susceptible to reproductive infidelity, such as the case with S. nicholsi and S. townsendi. However, more promising work has begun to elucidate alternative mate-choice factors, such as chemosensing in reproductive isolation in geckos (Zozaya et al 2019). Indeed, these findings are also consistent with a hypothesis of assortative mating in this system, which, without a behavioral or morphological barrier to reproduction, chemical signaling may play a role as well.…”
Section: Behavioral and Morphological Considerationssupporting
confidence: 66%
“…Under this LRC model, we can extrapolate that sexually monochromatic species that share a common mate-choice strategy may be more susceptible to reproductive infidelity, such as the case with S. nicholsi and S. townsendi. However, more promising work has begun to elucidate alternative mate-choice factors, such as chemosensing in reproductive isolation in geckos (Zozaya et al 2019). Indeed, these findings are also consistent with a hypothesis of assortative mating in this system, which, without a behavioral or morphological barrier to reproduction, chemical signaling may play a role as well.…”
Section: Behavioral and Morphological Considerationssupporting
confidence: 66%
“…Male lacertid lizards, including those of all Podarcis species, have specialized epidermal glands on the underside of their hind legs that exude waxy secretions, which are deposited as scent‐marks in the environment when lizards move through the habitat (Mayer, Baeckens, & Van Damme, 2015). Over the last decade, extensive behavioural assays combined with studies of natural products chemistry have revealed that the lipophilic compounds in these waxy secretions are important for lizard communication (Heathcote, Bell, d'Ettorre, While, & Uller, 2014; Khannoon, El‐Gendy, & Hardege, 2011; MacGregor et al, 2017; Pruett et al, 2016; Zozaya, Higgie, Moritz, & Hoskin, 2019). While an individual chemical compound can mediate social interactions as varied as territorial behaviour, male rival assessment and mate choice (Kopena, Martín, López, & Herczeg, 2011; Martín & López, 2006, 2007; Martín, Moreira, & López, 2007; Wyatt, 2014), in most cases the chemical signals of lizards are composed of a species‐specific mixture of multiple lipophilic compounds (Martín & Lopéz, 2014, 2015; Mayerl et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos que tiveram início no final dos anos 1980 e que se estendem até os dias de hoje, além de caracterizarem quimicamente as secreções femorais e pré-anais, demonstraram o seu papel nos mais diferentes contextos sociais de lagartos e buscaram compreender quais fatores estão associados às diferenças observadas. Secreções femorais e pré-anais já foram testadas em contextos de marcação de território, escolha de parceiros durante a estação reprodutiva, reconhecimento específico (BARBOSA et al, 2006), auto-reconhecimento, discriminação de indivíduos familiares e não familiares (ARAGÓN et al, 2001;FONT & DESFILIS, 2002), isolamento reprodutivo (GABIROT et al, 2013), identificação de complexos crípticos de espécies (GABIROT et al, 2012;ZOZAYA et al, 2019) e identificação do status de saúde e outras características de coespecíficos (CARAZO et al, 2007;HEATHCOTE et al, 2014;GARCÍA-ROA et al, 2017;NISA et al, 2019). Até o momento, diferentes fatores foram identificados influenciando diretamente a composição química das secreções das glândulas femorais e pré-anais, além de diferenças filogenéticas.…”
Section: Contexto Teóricounclassified
“…Ao contrário do observado para as fêmeas, há uma série de informações na literatura sobre a composição química das secreções femorais de machos. Conhecemos a composição lipídica de diversas espécies de Lacertidae (LÓPEZ & MARTÍN, 2005b;GABIROT et al, 2008;WELDON et al, 2008;GABIROT et al, 2010GABIROT et al, e 2012BAECKENS et al, 2017) e algumas espécies de outras famílias (ALBERTS et al, 1992b;ESCOBAR et al, 2001ESCOBAR et al, e 2003LOUW et al, 2007;KHANNOON, 2012;MARTÍN et al, 2016b;ZOZAYA et al, 2019). Alguns estudos demonstraram fatores que influenciam a composição química das secreções, seu papel no isolamento reprodutivo e na identificação de complexos crípticos de espécies e sua função em diferentes contextos sociais.…”
Section: Discussão Geral E Conclusõesunclassified
See 1 more Smart Citation